1974
DOI: 10.1192/bjp.124.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Cerebral Manifestations of Arteriosclerosis with Cyclandelate

Abstract: Despite controversy about whether cerebral arteriosclerosis is a valid clinical entity and independent of senile dementia and/or ‘functional’ senile psychoses (Post, 1971), there is a good reason for differentiating it in clinical practice, and its incidence is increasing (Registrar General, 1960).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

1975
1975
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…It was observed, however, that the decline was greater during the placebo phase than during the cyclandelate phase. No such decline during the course of the trial was noted in the present study, possibly because the patients in the present study began at a lower pretrial level than in the Young et al 15 study. Patients in that study actually began with an "average" IQ.…”
Section: Discussioncontrasting
confidence: 60%
“…It was observed, however, that the decline was greater during the placebo phase than during the cyclandelate phase. No such decline during the course of the trial was noted in the present study, possibly because the patients in the present study began at a lower pretrial level than in the Young et al 15 study. Patients in that study actually began with an "average" IQ.…”
Section: Discussioncontrasting
confidence: 60%
“…The clinical efficacy, unfortunately, has not been documented so clearly. Although several investigators have reported positive results (6–9), others have reported equivocal (10) or negative results (11). Nevertheless, it is apparent that in the past vasodilators have too often been prescribed indiscriminately, without proper selection of patients.…”
mentioning
confidence: 99%
“…The positive effect of cyclandelate on the attributes of impairment of recent memory, mood depression, irritability, hostility, indifference to surroundings and anxiety was significantly superior to that of placebo as early as the eighth week of treatment ( Table 2). (6)(7)(8)(9), others have reported equivocal (10) or negative results (11). Nevertheless, it is apparent that in the past vasodilators have too often been prescribed indiscriminately, without proper selection of patients.…”
mentioning
confidence: 99%
“…Cyclandelate has been used to treat patients with symptoms believed to be caused by cerebrovascular insufficiency, in addition to its more traditional use in treating various peripheral vascular disorders. Earlier studies of this drug predominantly evaluated its use in treating cerebral symptoms and showed that cyclandelate may offer improvement or delay in deterioration of certain symptoms of senility 6–10 . On the basis of these findings, researchers studied the drug's effects on other potential cerebrovascular symptoms: tinnitus, vertigo, and blurred vision.…”
mentioning
confidence: 99%